Patterns of Adsorption of Proteins From Human Plasma Onto Foreign Surfaces - Uniyal, S; Brash, J L (Thrombosis and Haemostasis, 1982)
The deposition of proteins on blood-contacting surfaces is known to be a determining factor in subsequent thromboembolic events. The composition of the protein layers and how they change with time are unknown. To generate information relevant to these questions, the quantities of albumin, fibrinogen and IgG adsorbed on seven surfaces from human plasma as a function of time were measured using a tracelabeling method. Materials studied include several segmented polyether-urethanes, glass, siliconized glass (SG), polystyrene (PS) and polyethylene (PE).Fibrinogen, surprisingly, was not adsorbed from plasma to any of the hydrophilic surfaces. On PE and SG adsorption passed through an early maximum (before 2 min) then declined to near zero. Only on PS was adsorption substantial and constant with time. Albumin was also not detected on the hydrophilic materials, but was adsorbed substantially on the hydrophobic surfaces. IgG was detected on all surfaces, although in relatively low surface concentrations.These results suggest: 1. that the plasma itself interacts with initially adsorbed proteins, 2. that the role of fibrinogen adsorption in foreign-surface initiated thrombosis may need to be reevaluated and 3. that since the major plasma proteins are only minimally adsorbed, trace proteins may be important in blood-material interactions.
Keywords: Blood-material interactions; Artificial surfaces; Plasma protein adsorption